Spanish literature teaching: what, why, how. - Calef, Paola (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2014)
Spanish literature teaching: what, why, how. This article is the result of my experience as a professor at the Spanish Literature Training course held in 2013 for the TFA students by the Department of Foreign Languages and Literatures and Modern Cultures by the University of Turin and partially reflects the themes which the students were to elaborate during their training and the resulting considerations. This article, just as the course, is not meant to expand the subjet area, but rather to inquire the disciplinary subject, its educational aims and teaching methodologies, in the firm belief that such inquiring should always accompany the daily practice of a teacher.